Demountable shear wall with rocking boundary columns for precast concrete buildings in high seismic regions. (July 2022) - Naserpour, Afshin; Fathi, Mojtaba; Dhakal, Rajesh P.
Abstract: In this paper, a Demountable shear Wall with Rocking Column (DWRC) system is proposed. The purpose of the DWRC system is to ensure that the demountable shear walls are damaged while the boundary columns remain resilient. To increase the system's energy dissipation capacity, a series of steel slit dampers are placed at the rocking column bases and vertical joints of the walls. Also, instead of a large wall, several smaller walls are used in each story. To evaluate the behavior of the DWRC system, 15 models of 3, 9 and 15-stories are studied. At each height level, four DWRC models, with various numbers of steel dampers per vertical joints of walls, are compared to a conventional shear wall model. After developing numerical models, nonlinear cyclic and time history analyzes are performed. The results reveal that with the introduction of rocking boundary columns, all plastic strains are concentrated in demountable walls and steel dampers, while the columns remain undamaged. Also, by using slender walls for the DWRC system, plastic strains are distributed with less intensity in walls of all stories. Due to these results, for DWRC models, maximum value of inter-story drift, floor acceleration and residual displacement are reduced by 14%, 24% and 27%, respectively, compared to the conventional shear wall model.